2002
DOI: 10.1007/s00421-002-0653-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise induces gastrointestinal leakage of allergen in lysozyme-sensitized mice

Abstract: Food-dependent exercise-induced anaphylaxis (FDEIAn) is a leading cause of physical allergies. However, the mechanisms involved in the development of FDEIAn are not yet clearly understood. In this study, to investigate the leakage of allergen from the gastrointestinal tract into the circulation, lysozyme (LYZ)-sensitized B10.A mice, which have been shown to exhibit an especially high concentration of plasma antigen-specific immunoglobulin-E (IgE) by sensitization of LYZ as allergen in the white of hens' eggs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 21 publications
4
35
0
1
Order By: Relevance
“…reduced the physical activity of the sensitized mice, and this effect continued for about 7 h. A decrease in physical activity in sensitized mice is an indicator of the presence of allergen, as described previously. 19) Our result, that no antigenic activity of OVA was detected in the portal blood of mice administered H-C OVA and that anaphylaxis symptoms were repressed in sensitized mice administered H-C OVA, indicate that heat-coagulated protein is not an allergen. Astwood et al reported that important food allergens were not digested in simulated gastric fluid, and that this stability is a significant and valid parameter for distinguishing food allergens from non-allergens.…”
Section: )mentioning
confidence: 59%
“…reduced the physical activity of the sensitized mice, and this effect continued for about 7 h. A decrease in physical activity in sensitized mice is an indicator of the presence of allergen, as described previously. 19) Our result, that no antigenic activity of OVA was detected in the portal blood of mice administered H-C OVA and that anaphylaxis symptoms were repressed in sensitized mice administered H-C OVA, indicate that heat-coagulated protein is not an allergen. Astwood et al reported that important food allergens were not digested in simulated gastric fluid, and that this stability is a significant and valid parameter for distinguishing food allergens from non-allergens.…”
Section: )mentioning
confidence: 59%
“…27, 39). Similar to the effects of exercise on biotransformation in hepatocytes (59), swimming increased transcripts of certain intestinal genes, e.g., UDPglucuronosyltransferase (Udpgtr2), glutathione S-transferase (Gsto2), and paraoxonase (Pon1), which could neutralize xenobiotics and protect the body from toxic substances (11,44,56).…”
Section: Discussionmentioning
confidence: 82%
“…This indicates at least additional other mechanisms of action, because clinical observation shows that the intensity of exercise necessary to trigger FDEIA in humans varies quite tremendously from exercise near exhaustion to very mild. Interestingly, a mouse study on gastrointestinal lysozyme uptake showed that not only exercise but also lysozyme-specific sensitization significantly upregulated intestinal absorption and that sensitization and exercise together synergistically increased this uptake demonstrating the interdependence of IgE reactivity and exercise (31). In conclusion, available data indicate the following scenario: the intensity of exercise and the degree of sensitization coregulate the intestinal absorption of allergens with the consequence of orchestrating anaphylaxis each on an individual level.…”
Section: Exercise As Cofactor Of Anaphylaxismentioning
confidence: 94%